Protein kinase C isozymes epsilon and alpha in murine erythroleukemia cells. - Powell, C T (1992)
Protein kinase C (PKC) has a role in signal transduction during hexamethylene bisacetamide (HMBA)-induced differentiation of murine erythroleukemia cells (MELC). Separation of MELC PKC isozymes by hydroxylapatite chromatography yields a major peak (III) and a minor peak (II) of PKC activity, previously reported to contain the PKC alpha and beta isozymes, respectively. In the present study, we confirm that peak III activity is PKC alpha but show that peak II contains PKC epsilon and little or no PKC beta. Immunoblot analysis with isozyme-specific anti-alpha and anti-epsilon PKC antibodies detected PKC alpha in peak III and PKC epsilon in peak II. Peak III activity was markedly enhanced (up to 20-fold) by phosphatidylserine, diolein, and Ca2+, whereas addition of these cofactors to the reaction mixture stimulated peak II activity only 2- to 4-fold. RNase protection analysis of MELC RNA showed that PKC alpha and PKC epsilon RNAs were in a ratio of approximately 2:1, but PKC beta RNA was barely detectable. Taken together, these data indicate that MELC contain PKC alpha and PKC epsilon but little or no PKC beta.